Analysis of Pierce's Semiotic Perspective in the Terminology of Nahwu - Ucu Siti Shafa Zakiah; Asep Sopian; Al-Rawafi Abdulkhaleq (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This research is motivated by many Arabic Language students who only understand the terms of grammatical function in Nahwu, yet not with the essence of its meaning. Therefore, this research researches one of the books in the past - that keeps much secret knowledge - with semiotic studies as part of the linguistic form and educational value analysis. The purpose of the research is to recognize the icons, indexes, and symbols that had been used by Imam Ibnu Ajibah as the interpretation of terms in Nahwu and to know the value of education in this book. The research method that is used is qualitative descriptive with Pierce semiotic approach and literature review technique for research data collection. This research's primary data source is from Al-Futuhaat Al-Quddusiyah Fi Syarhi Muqaddimati Al-Jurumiyyah book created by Imam Ibnu Ajibah. The result of this research shows that there are two icons in the book: Tasawuf/Sufism (teachings on how to get closer to Allah and be united with Him) expert and the second one is what Sufi people do. Three indexes are also recognized: the speaking behavior index, behavior of a Salik index, and jihad behavior index. The six symbols inside the book are the Asma Allah symbol, the procedure of the Wushul symbol, the Ma'rifat symbol, the saints' oath symbol, the Jihad symbol, and the unseen symbol. The value of education in the book includes tawhid education values - which are Rububiyyah Tawhid and Asma wa Sifat Tawhid - and moral education values - which are morals towards Allah, Rasulullah, and morals towards human beings in their personal and social environment state-.